Nitrite/nitrate and malondialdehyde levels in nasal polyp - Bugdayci, G.; Kaymakci, M. (Cellular and Molecular Biology, 2008)
The aim of this study was to examine the pathophysiological role of NO (nitric oxide) and MDA (malondialdehyde) in tissue in patients with nasal polyposis. We measured nitrite/nitrate (Nitrite/Nitrate; NO2-/NO3-) and MDA in tissue and plasma of NP patients (n=20) and controls (n=20). MDA level expressed as the concentration of substances reacting to thiobarbituric acid and production of NO (concentration of nitrite/nitrate in plasma) by the Griess reaction were determined. The level of NO2- and NO3- in tissue are higher than that of the normal tissue (p<0.05). The level of MDA in tissue are higher than that of the normal tissue (p<0.05). The level of NO2- and NO3- in plasma of two groups are similar (p>0.05). The level of MDA in plasma is higher than that in the normal controls (p<0.05). The change in NO2-/NO3- and MDA levels of nasal polyp patients was demonstrated. Further studies are required concerning the significance of changes in lipid peroxidation and nitrite levels in pathogenesis of nasal polyp.